Region‐dependent and stage‐specific effects of stress, environmental enrichment, and antidepressant treatment on hippocampal neurogenesis. Issue 9 (22nd May 2013) - Tanti, Arnaud; Westphal, Willy‐Paul; Girault, Virginie; Brizard, Bruno; Devers, Severine; Leguisquet, Anne‐Marie; Surget, Alexandre; Belzung, Catherine
ABSTRACT Chronic stress and depression are associated with decreased levels of hippocampal neurogenesis. On the other hand, antidepressants as well as environmental enrichment may rely in part on their pro‐neurogenic effects to improve cognition and mood. Because a functional heterogeneity has been consistently reported along the septo‐temporal axis of the hippocampus, regional changes in neurogenesis could differentially contribute to these effects and affect distinct hippocampal functions. Mapping these regional changes could therefore provide a better understanding of the function of newborn neurons. While some studies report region‐specific effects of stress and antidepressants on neurogenesis, it is unclear whether these changes affect distinct populations of newborn neurons according to their developmental stage in a region‐specific manner. By using endogenous markers and BrdU labeling we quantified the regional changes in cell proliferation and survival as well as in the number of neuronal progenitors and immature neurons following unpredictable chronic mild stress (UCMS), environmental enrichment (EE) and chronic fluoxetine (20 mg/kg/day) treatment along the septo‐temporal axis of the hippocampus. EE promoted cell proliferation and survival of 4‐week‐old newborn cells as well as increased the number and proportion of post‐mitotic immature neurons specifically within the septal hippocampus. By contrast, UCMS uniformly decreased cell proliferation, survival and immature newborn neurons but differentially affected progenitor cells with a decrease restricted to the temporal regions of the hippocampus. Whereas fluoxetine treatment in control mice affected proliferation and survival specifically in the temporal hippocampus, it reversed most of the UCMS‐induced alterations all along the septo‐temporal axis. These results highlight that different factors known for exerting a mood improving effect differentially regulate neurogenesis along the septo‐temporal axis of the hippocampus. Such region and stage specific effects may correlate to distinct functional properties of newborn neurons along the septo‐temporal axis of the hippocampus which may contribute differently to the pathophysiology of affective disorders. © 2013 Wiley Periodicals, Inc.